1986
DOI: 10.1136/oem.43.8.544
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory uptake and elimination of ethylene glycol monoethyl ether after experimental human exposure.

Abstract: Ten male volunteers were exposed to ethylene glycol monoethyl ether (EGEE) under various conditions of exposure concentration and physical workload. Steady state levels of retention, atmospheric clearance, and rate of uptake were reached immediately after the start of the exposure period for all experimental conditions. Retention was high (64% in resting condition) and increased as physical exercise was performed during exposure. Atmospheric clearance increased as the pulmonary ventilation rate increased. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 9 publications
0
20
0
3
Order By: Relevance
“…Our recent paper also showed that subjects recovered very quickly from the 2-ME-induced hematological effects as the airborne concentrations of 2-ME and its major toxic metabolite, MAA (2-methoxy acetic acid), were reduced 35,36) . Since the half-life of MAA in humans (77-100 h) [37][38][39] is much longer than that of EAA (23-42 h) 40,41) , we speculate that the toxic metabolite, EAA, stays in humans a shorter time than MAA, and human subjects can recover more quickly from the 2-EEA-induced hematological effects than those induced by 2-ME. Since increasing temporal trends of hemoglobin, haematocrit, and the RBC count were found in this study for the exposed workers during the followup period, these findings suggest that reducing exposures through dermal contact can lead to the gradual amelioration of the hematological effects in 2-EEAexposed workers.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent paper also showed that subjects recovered very quickly from the 2-ME-induced hematological effects as the airborne concentrations of 2-ME and its major toxic metabolite, MAA (2-methoxy acetic acid), were reduced 35,36) . Since the half-life of MAA in humans (77-100 h) [37][38][39] is much longer than that of EAA (23-42 h) 40,41) , we speculate that the toxic metabolite, EAA, stays in humans a shorter time than MAA, and human subjects can recover more quickly from the 2-EEA-induced hematological effects than those induced by 2-ME. Since increasing temporal trends of hemoglobin, haematocrit, and the RBC count were found in this study for the exposed workers during the followup period, these findings suggest that reducing exposures through dermal contact can lead to the gradual amelioration of the hematological effects in 2-EEAexposed workers.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity also led to increased uptake. With equivalent doses, retention of 2-ethoxyethyl acetate was always somewhat lower than retention of 2-ethoxyethanol (Groeseneken et al 1986a); this was attributed to the slightly lower water solubility of the acetate. The amount of unmetabolized 2-ethoxyethyl acetate exhaled was < 0.5 % of the total amount absorbed.…”
Section: Experimental Exposurementioning
confidence: 96%
“…A maximum of 0.4 % of the absorbed dose was exhaled unchanged. Apart from 2-ethoxyethanol, no other volatile organic compounds were detected in the exhaled air (Groeseneken et al 1986a).…”
Section: Experimental Exposurementioning
confidence: 99%
“…Dies bedeutet, daß die im Körper verbleibende Menge an 2-Ethoxyethanol allein eine Funktion der Raumluftkonzentration, des Atemzeitvolumens, des Hautkontaktes und der Dauer der Exposition ist und daß eine Sättigung der Kompartimente des menschlichen Körpers durch Ethoxyethanol nicht eintritt (17). Dies ist eine Folge des Verteilungsgleichgewichtes des 2-Ethoxyethanols zwischen Blut und Luft, das ganz auf der Seite des Blutes liegt.…”
Section: Metabolismus Und Kinetikunclassified
“…In diesem Zusammenhang kommt der Arbeit von Groeseneken und Mitarbeitern (17,18) besondere Bedeutung zu. Diese Autoren haben fünf Probanden bei gleichzeitiger unterschiedlicher körperlicher Belastung definierten Ethoxyethanol-Konzentrationen ausgesetzt.…”
Section: Beziehung Zwischen äUßerer Und Innerer Belastungunclassified